Importance of Medical Plants and Herbs - Mandal, Saroj Kumar; Soren, Rosline (American Journal of Biology and Natural Sciences, 2025)
The use of medicinal plants has been done since ancient times and may be considered the origin of modern medicine. Compounds of plant origin have been and still are an important source of compounds for drugs. In this study a bibliometric study of all the works indexed in the Scopus database until 2019 has been carried out analyzing more than 100,000 publications. On the one hand, the main countries, institutions and authors researching this topic have been identified, as well as their evolution over time. On the other hand, the links between the authors, the countries and topics under research have been analyzed through the detection of communities. The last periods, from 2009 to 2014 and from 2015 to 2019, have been examined in terms of research topics. It has been observed that the areas of study or clusters have been reduced, those of the last period being those engaged in unclassified drugs, traditional medicine, cancer in vivo study, antidiabetic activity, and animal anti-inflammatory activity. In summary, it has been observed that the trends in global research are more on search for new medicines or active compounds rather than on the cultivation or domestication of plant species with this demonstrated potential.